Speckle tracking approaches in speckle sensing - Charrett, Thomas O. H.; Kotowski, Krzysztof; Tatam, Ralph P. (SPIE, 2017)
This paper reports some initial investigations into the application of feature tracking algorithms as an alternative data processing method for speckle correlation sensors capable of determining both the speckle pattern translation and rotation. The accuracy of translation measurements using the feature tracking approach was found to be similar to that of correlation based processing with accuracies of < 0.04 pixels. Rotation measurement accuracies of< 0.05 ◦ are found to be achievable over angle range ±20 ◦ , limited by the failure to match speckles at larger rotation angles.
Keywords: Laser Speckle; Feature matching; Feature tracking; Translation measurement; Rotation measurement